Natural alleles of GLA for grain length and awn development were differently domesticated in rice subspecies japonica and indica. Issue 8 (9th March 2019) - Zhang, Yanpei; Zhang, Zhanying; Sun, Xingming; Zhu, Xiaoyang; Li, Ben; Li, Jinjie; Guo, Haifeng; Chen, Chao; Pan, Yinghua; Liang, Yuntao; Xu, Zhijian; Zhang, Hongliang; et al.
Summary: Rice ( Oryza sativa L.) cultivars harbour morphological and physiological traits different from those of wild rice ( O. rufipogon Griff.), but the molecular mechanisms underlying domestication remain controversial. Here, we show that awn and long grain traits in the near‐isogenic NIL‐GLA are separately controlled by variations within the GLA ( Grain Length and Awn Development ) gene, a new allele of GAD1 / RAE2, which encodes one member of the EFPL (epidermal patterning factor‐like protein) family. Haplotype analyses and transgenic studies revealed that InDel1 (variation for grain length, VGL) in the promoter region of GLA ( GLA VGL ) increases grain length by promoting transcription of GLA . Absence of InDel3 (variation for awn formation, VA) in the coding region (CDS) of GLA ( GLA va ) results in short awn or no awn phenotypes. Analyses of minimum spanning trees and introgression regions demonstrated that An‐1, an important gene for awn formation, was preferentially domesticated and its mutation to an‐1 was followed by GLA and An‐2 . Gene flow then occurred between the evolved japonica and indica populations. Quality analysis showed that GLA causes poor grain quality. During genetic improvement, awnlessness was selected in ssp. indica, whereas short–grained and awnless phenotypes with good quality were selected in japonica . Our findings facilitate an understanding of rice domestication and provide a favourable allele for rice breeding.